Enrichment of bioactive minor components from CPO and PPMFO by sequential adsorption-desorption technique - Phoon, Kah Yee (2018)
The effort to separate or enrich bioactive compounds such as Vitamin E, phytosterols, squalene, and carotenoids from natural resources has been made to fulfil the increasing demands of the global market. Crude palm oil (CPO) which extracts from the palm oil fruit mesocarp fibre, is the product of palm oil mill, while, palm-pressed mesocarp fibre oil (PPMFO) is the residual oil of palm-pressed mesocarp fibre, a solid biomass which produced after CPO extraction in palm oil mill. Numerous studies reported on the presence of bioactive compounds as the minor components in CPO and PPMFO. In order to fulfil the market demand of these minor components, attempts such as supercritical fluid extraction and molecular distillation were develop to separate the minor components from plant source. However, limitation are present in current separation process. Therefore, in this study, interest is focusing on the enrichment efficiency of the minor components from CPO and PPMFO through a proposed sequential adsorptiondesorption technique. Initially, static adsorption-desorption test was carry out to evaluate the adsorption and desorption efficiency using six commercial mesopores adsorbents which represented different polarity towards the minor components that obtained from CPO. Non-polar adsorbents (Diaion HP20 and Sepabeads SP850) showed better adsorption-desorption efficiency than polar adsorbent (silica gel and Florisil) and weak polar adsorbent (Diaion HP2MG and Amberlite XAD-7HP) due to the similar polarity between the minor components and adsorbent. Diaion HP20 was selected as the best adsorbent resulting of the economic price and it can be stored at room temperature compared with Sepabeads SP850. Then, CPO was adsorbed by Diaion HP20 and placed into a Soxhlet extraction system to perform sequential adsorption-desorption process study. Three different organic solvent were used in the sequential adsorption-desorption process study to investigate the effect of desorption solvent and desorption time towards the enrichment efficiency of minor components. After obtaining the best process parameters, the sequential adsorption-desorption process were repeated by subjecting PPMFO as the feedstock. Under the same process parameters, Vitamin E, phytosterols, and squalene from CPO were obtained in the 1st fraction using methanol with desorption time of 4 h that gave enrichment factor (EF) of 3.4, 3.9, and 1.8, respectively, which slightly higher than those minor components obtained from PPMFO, 1.2, 1.8, and 1.4,respectively. Meanwhile, the carotene obtained from both CPO and PPMFO was enriched in the 3rd fraction by using n-hexane with an enrichment factor of 1.1 and 1.5, respectively. In conclusion, the obtained result revealed the efficiency of the proposed sequential adsorption-desorption technique to enrich the minor components from CPO and PPMFO.